Spatial working memory in hypothyroidism – an observational study on different ranges of thyroid stimulating hormone - Jhandi, Satkarjit Kaur; Shenoy, Shweta; Singh, A. P.; Singh, Ajaypal (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Hypothyroidism is associated with cognitive impairments. Clinically, subclinical hypothyroidism (SCH) is very common and patients often experience symptoms such as forgetfulness or memory deficits. Despite achieving normal thyroid stimulating hormone (TSH) levels through levothyroxine (LT-4) treatment, patients still report persistent complaints of lack of memory. Previous imaging studies have shown abnormalities in some cognitive domains, particularly in spatial working memory (SWM), that are characteristic of SCH. Therefore, the current study aimed to investigate SWM function across different ranges of TSH in patients with SCH. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This cross-sectional study included a total of 136 participants. Group 1: 36 controls, group 2: 33 newly diagnosed patients with SCH (TSH levels ≥2.5 mIU/L), group 3: 32 patients with SCH (elevated TSH levels ≥4.0 mIU/L) having L-T4 treatment, group 4: 35 euthyroid (TSH levels <4.0 mIU/L) but ongoing LT-4 treatment. The SWM task was performed for an assessment of SWM function, using a computerized battery (Cambridge Neuropsychological Test Automated Battery-CANTAB). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Our results report a statistically significant difference in the key parameters of SWM task among all groups. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Our findings indicate that patients with SCH show better performance in SWM when their TSH levels decrease with LT-4 treatment, in comparison to patients who were newly diagnosed. The present study suggests a TSH level of 2.5 mIU/L may be the optimal threshold for initiating LT-4 treatment in patients with SCH.